Hubungan Manajemen Model Asuhan Keperawatan Profesional Tim Dengan Kualitas Pelayanan Keperawatan di Ruang Rawat Inap Rumah Sakit Islam Sultan Agung Semarang - Pipit Diansari; Muh.Abdurrouf; Dyah Wiji Puspita Sari (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
The quality of nursing care is reflected in the implementation of professional nursing care. Professional and qualified nurses must possess both hard skills and soft skills, as success in the workplace is influenced by soft skills (80%) and hard skills (20%). Indonesia still faces many challenges in achieving nursing care quality that reflects professional practice. The way nursing care is provided is not entirely focused on meeting the client's needs but is more oriented toward task completion. The purpose of this study is to determine the relationship between the professional team nursing care model and the quality of nursing care in the inpatient ward. This is a quantitative study using a correlational approach with a cross-sectional design. The study sample consisted of 146 respondents using purposive sampling. Data analysis utilized the Spearman rank correlation technique. The respondents were predominantly female, held a bachelor's degree, and had less than five years of work experience. Most of the MAKP met the criteria, and most reported that the quality of care was good. Based on bivariate analysis, a significant relationship was found between MAKP and the quality of inpatient care at RSI Sultan Agung Semarang. This result is shown by a correlation coefficient of 0.807 with a positive relationship and a significance value of 0.000 (p-value < 0.05). There is a significant relationship between MAKP and the quality of inpatient care services at RSI Sultan Agung Semarang.